Mayo Clinic on High Blood Pressure - Sheps, Sheldon (Estados Unidos: Mayo Clinic Heallth, 1999)
Contiene información como llevar una buena salud y así evitar enfermedades futuras
CONTENIDO Chapter 1. Understanding high blood pressure Chapter 2. Are you at risk Chapter 3. Diagnosis and treatment Chapter 4. Controlling your weight Chapter 5 Getting more active y otros ...
Incluye índice
Keywords: SALUD -- PREVENCIÓN; PRESIÓN ALTA